Floral Distribution, Diversity, and Ecology of Mangrove Forests in Mandaitivu and Arali, Sri Lanka - Ahalya Arulnayagam (CV. Literasi Indonesia, 2020)
Mangroves in the northern parts of Sri Lanka have been understudied and often ignored by the ecologists due to several reasons. This paper contributes to the assessment of floristic diversity and community structure of mangrove forests in two sites in the Northern Province; Mandaitivu and Arali. Vegetation studies were undertaken with the use of 10m wide belt transect laid across the water-land gradient, within which, 5-7 quadrats were placed for floral identification (nMandaitivu = 67, nArali = 44). Subsurface water samples (n=57) from the adjacent estuarine region were taken to assess environmental parameters. Ten true mangrove species of six families were identified altogether in both sites. Bruguiera cylindrica, Lumnitzera racemosa, Excoecaria agallocha and Avicennia marina showed higher niche width. Zonation exhibited Rhizophora in the fringing zone, Avicennia landward and the others in the mixed zone. Salinity in both areas was relatively high and showed a significantly positive correlation with mangrove abundance along with conductivity, tidal regime and pH. Despite their important role in coastal dynamics, mangroves have been degraded due to anthropogenic activities, thus demanding actions for conservation in the future.